Open Defecation Free (ODF) as One Urgent of Community-Based Total Sanitation Program in Abeli Primary Healthcare, Kendari - Syefira Salsabila; Rizki Eka Sakti Octaviani; Rahman; Maryam Iskandar; Rahmatia (Universitas Muhammadiyah Malang, 2023)
The Community-Based Total Sanitation (STBM) Program in Indonesia is one of the efforts to overcome sanitation problems. The relationship between sanitation and stunting is that poor sanitation causes some of the most severe diseases that can lead to chronic bacterial infections that make nutrients difficult to absorb. This condition usually reduces appetite, resulting in lower nutrient intake and diverting energy for growth to fight off the body's resistance to infection. This study uses a qualitative descriptive method using an empirical approach. This research was carried out in the working area of the Abeli ealth Center, Kendari City, from May to June 2021. This study explains that employees have tried to implement government regulations regarding this ODF by referring to the regulations of the mayor of Kendari. Employees at the Puskesmas always socialize this ODF in collaboration with the local headman and cooperation within the Bappeda Kendari. This coordination is carried out in the program to eradicate open defecation, especially in coastal areas. This activity is highly highlighted by the government to achieve the target of the Healthy City. So that in 2019 all areas in Kendari City have received the ODF declaration. Kata kunci : STBM, Open Defecation Free, Sanitation